Construing Worst Experiences of the COVID-19 Pandemic in the USA: A Thematic Analysis. Issue 1 (2nd January 2023) - Winter, David A.; Brunet, Alain; Rivest-Beauregard, Marjolaine; Hammoud, Razan; Cipolletta, Sabrina
Abstract: The COVID-19 pandemic has not only resulted in millions of deaths but, together with the strategies imposed to contain the spread of the disease, it has had significant psychological and social effects. This paper considers these effects in residents of the USA, the country that has reported the highest number of deaths from COVID-19. Between April and May, 2020, responses were obtained to an on-line survey, which included asking participants, recruited by snowball sampling, to describe their worst experience of the pandemic. The responses of 741 participants, primarily female and Caucasian, were subjected to a thematic content analysis which used a primarily deductive approach in which these responses were viewed in terms of transitions in construing. The transition themes identified were anxiety; threat; loss of role; sadness; contempt; and stress. Various subthemes were also identified. The study provided further evidence of the utility of a personal construct framework in conceptualizing experiences associated with illness and the risk of this. Implications of its findings are considered at both an individual and a societal level.